The pocket guide to Every Child Matters : an at-a-glance overview for the busy teacher - Cheminais, Rita (Routldedge, Taylor & Francis Group, 2010)
The aim of this pocket guide is to provide an at-a-glance overview and insight into Every Child Matters for busy trainee, newly qualified and experienced teachers.